Beyond ridiculous making gay theatre with Charles Busch in 1980s New York - Elliott, Kenneth 1929-2011 (University of Iowa Press, 2023)
"Beyond Ridiculous tells the story of Theatre-in-Limbo, a downtown band of actors formed in 1984 by playwright and soon-to-be drag legend Charles Busch, and director Kenneth Elliott. They performed Vampire Lesbians of Sodom at the Limbo Lounge, a raffish club in the East Village, then considered a dangerous corner of the New York City. But the next year, the show moved to the historic Provincetown Playhouse, a commercial Off-Broadway venue, and famously became the longest-running nonmusical in Off-Broadway history. From 1984 to 1991, Busch starred in eight Limbo productions, always in proud, outrageously fabulous drag. Yet ironically, Busch would eventually become a beloved grand dame of the New York theatre establishment, even including forays onto Broadway. In Beyond Ridiculous, Elliott, Limbo's director, producer, and co-founder, narrates in first-person the company's Cinderella tale of fun, heartbreak, and dishy drama. Scenes include the ecstatic opening night of Vampire Lesbians, complete with a production assistant rushing backstage with a hot-off-the-presses rave from The New York Times; encounters with Todd Rundgren, Joe Papp, and Milton Berle; but also, a thorough analysis of Busch's plays and a vivid account of the now-vanished gay New York theatrical scene of the 1980s. At the center of the book is the young Charles Busch, an unforgettable personality fighting to be seen, be heard, and express his unique style as a writer-performer in plays such as Psycho Beach Party and The Lady in Question. The tragedy of AIDS among treasured friends in the company, the struggle for mainstream acceptance of LGBTQ theatre during the reign of Reagan, and the exploration of new ways of being a gay theatre artist make the book a heartwarming, bittersweet, but ultimately joyous, ride. With queer rights under fire, remembering this inspiring moment in LGBTQ theatre history isn't just important, it's essential"--
Keywords: Elliott, Kenneth; Busch, Charles; Theatre-in-Limbo (Theater company) / History; Theatrical companies / New York (State) / New York / History / 20th century; Gay theater / New York (State) / New York / History / 20th century; Troupes de théâtre / New York (État) / New York / Histoire / 20e siècle; Théâtre homosexuel / New York (État) / New York / Histoire / 20e siècle; Theatrical companies; New York (State) / New York; Gay art; Gay theater groups; Gay men; 1900-1999; History